Effect of chemical and biological degumming on the adsorption of heavy metal by cellulose xanthogenates prepared from Eichhornia crassipes - Deng, L.; Geng, M.; Zhu, D.; Zhou, W.; Langdon, A.; Wu, Hongwei; Yu, Yun; Zhu, Z.; Wang, Y. (Elsevier BV, 2012)
Cellulose xanthogenates, derived from the straw of Eichhornia crassipes, were prepared as adsorbents for heavy metals by CS2 sulfonation and magnesium substitution after degumming with alkali, self-isolated A1 strain and pectase, respectively. The effects of three degumming treatments were compared by functional groups analysis, surface morphology and surface element composition and heavy metal (Pb2+) adsorption studies. The results demonstrate that bio-degumming treatments by A1 strain and pectase have weaker degumming effects than alkali treatment. However, the surface characteristics of the bio-degumming products, especially the pectase degumming product, are more beneficial to heavy metal adsorption. In comparison to that of the raw plant materials, the Pb2+ adsorption performances of the three xanthogenates improved significantly, although no obvious differences being observed among themselves. From an environmental point of view, the two bio-degumming treatments, especially the pectase degumming treatment, are more beneficial to prepare heavy metal adsorbents than the alkali degumming treatment.